Onychocryptosis: A review of epidemiology, risk factors, classification, complications and effective therapeutic strategies. - Pawlik, Paweł; Zaroda, Przemysław; Dąda, Paweł; Niewinna, Patrycja; Żuchowski, Michał; Mańdziuk, Dominika; Kołodziej, Klaudia; Kołodziej, Wojciech; Wawrzkowicz, Jakub; Korga, Monika; Panuciak, Kinga (Journal of Education, Health and Sport, 2024)
Abstract: Ingrown toenails, clinically known as onychocryptosis, represent a prevalent nail pathology. The clinical manifestation involves symptoms typical for a foreign body reaction and in severe cases, tissue hypertrophy with complications may occur. Key risk factors include improper nail care, trauma, obesity, tight footwear, poor foot hygiene, and genetic predisposition. The condition predominantly affects individuals between the first and the third decades of life and older adults, with a predilection for the great toe, especially the lateral skin fold. The Heifetz and Scholz classifications delineate the stages of ingrown toenails based on severity. Therapeutic approaches range from conservative procedures, such as taping, dental floss, gutter treatment, cotton nail cast, braces and super elastic wire to surgical interventions like partial or total nail avulsion, matricectomy and advanced techniques like the Vandebos procedure or the Winograd procedure. Although many studies have analysed available treatment methods, there is no consensus among specialists regarding the best therapeutic strategy. Complications include paronychia, infection, and scarring. A comprehensive therapeutic approach should consider clinical severity, patient preferences, and both conservative and surgical interventions, emphasizing the importance of larger randomized clinical trials to establish definitive guidelines.